Problematika Kepastian Hukum dalam Sistem Pendaftaran Merek: (Studi Putusan Mahkamah Agung Nomor 989K/Pdt.Sus-HKI-2024) - Khumayro Khumayro; Diana Tantri Cahyaningsih (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the application of the first to file principle on the cancellation of the registered trademark “Tako” in the Supreme Court Decision Number 989K/Pdt.Sus-HKI/2024. This research is a prescriptive normative legal research using statute approach and case approach. The results of this study indicate that the judge's consideration in the Supreme Court Decision Number 989K/Pdt.Sus-HKI/2024 to cancel the registered mark “Tako” owned by the Defendant/Case Respondent for bad faith based on the existence of similarities in essence with Perguruan Tako who first used the mark is contrary to the principle of first to file adopted by Indonesia because Perguruan Tako is not a well-known and unregistered trademark so as to cause legal uncertainty and ignore external legal protection to the Defendant/Case Respondent as the owner of the registered mark “Tako”.